Leadership Positions and Leadership Types in Work Setting: The Role of Gender - Koutsioumpa, Eftichia (Technium Business and Management, 2023)
Introduction: Leadership is a multifaceted and socially driven phenomenon that manifests in diverse contexts, most notably within professional work. The research has focused on examining the impact of racial discrimination on the assumption of leadership roles inside the workplace. Objective: This study aims to investigate the workplace challenges associated with the identification of appropriate candidates for leadership roles, with a specific focus on the influence of gender in this process. Additionally, an examination was conducted to investigate the impact of various leadership styles on the performance of individuals in the workplace. Method: The present study comprehensively examines the scholarly works published between 2019 and 2023. The selection criteria employed in this study encompassed the requirement for articles to be written in English, possess a substantial connection to the subject domain of leadership, and be grounded in either quantitative or qualitative research methodologies. Following a comprehensive and rigorous assessment of the articles, 12 were incorporated into the study. Findings: The existing research on diverse leadership styles and their relationship with gender is quite scarce. Our study encompasses twelve publications, with five studies explicitly focusing on various leadership styles and the remaining seven articles examining the impact of gender on leadership. Gender discrimination plays a role in influencing the selection of specific individuals for advancement to higher positions. The gender of their supervisor might influence the perception of leadership actions among subordinates. In general, existing data indicates that gender biases and stereotypes persistently influence the formation of perceptions and expectations around leadership positions. Nevertheless, there are signs of shifting gender perceptions and diminished gender biases inside leadership positions. The significance of supervisors and their assistance in cultivating leadership aspirations is paramount. The promotion of gender equality in leadership roles necessitates the recognition and rectification of gender prejudices, hence underscoring the need to challenge and overcome such biases.